Transformasi Spasial di Kawasan Peri Urban Kota Malang - Mahendra, Yusril Ihza; Pradoto, Wisnu (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Limited land in the centre of the city will encourage people to choose residing in the suburb area as alternative, which of course also effect transformation in those areas. Spatial transformation that occured in peri-urban area will change the pattern of space utilization existed in that region. The population growth rate of Malang city is approximately 0,86% larger than that in East Java (0,75%). The increasing number of population growth in Malang occured unevenly in all parts of the city. The purpose of this research is to review the spatial transformation occuring in peri-urban area of Malang city by firstly analyzing the location of peri-urban based on its land usage. The analysis is conducted with geographic information system ArcGis 9.3, which is benefited to analyze map overlay dan kernel density analyze. Based on the result of analysis, it is discovered that there is a difference of spatial transformation between the north and south region of peri-urban areas in Malang city. Kedung Kandang district, which is located in the south region, experienced a low transformation with a linier trend of developing land pattern. Meanwhile, Lowokwaru district is experiencing high transformation with a concentric trend of developing land pattern. This difference occured due to several factors, which are population factor like high growth population, center of activity, accessibility, the role of developer, and policy factor related with direction of spatial region patter.The trend of distribution pattern in population density and developed land aimed on the northern part of the city indicated the direction of the city development trend.